A rare case of pregnancy with primary spontaneous pneumothorax posted for emergency cesarean section - Laltanpuii Sailo; Stephen L Sailo (Wolters Kluwer Medknow Publications, 2020)
Spontaneous pneumothorax during pregnancy is a rare condition. Only 56 cases have been reported in the English literature. A primigravida at 32 weeks pregnancy presented with breathing difficulty, left chest pain, and cough for 2 days. She was diagnosed to have left primary spontaneous pneumothorax and multiple unruptured blebs and bullae of the right lung. A left chest tube was inserted which relieved her symptoms. However, after 3 weeks, she again developed breathing difficulty so she was planned for an emergency cesarean section. The anesthesia was challenging as she could lie down only in the 60° propped-up position. With spinal anesthesia, desired level of block could not be achieved. General anesthesia also could not be given as it will cause further rupture of blebs and bullae. Therefore, the operation was performed under epidural anesthesia using injection ropivacaine in the same 60° propped-up position.